Cross-readings and ecoliteracy in children's pop-up books - Ramos, R. (2014)
The purpose of this text is to analyse two recently been published pop-up books aimed at children, by Anouck Boisrobert e Louis Rigaud, Popville (2009) and Dans la forêt du paresseux [Wake up, Sloth!, En el bosque del perezoso] (first published in 2009 and 2012, accompanied with texts by Joy Sorman and Sophie Strady, respectively). These books were published originally in France by Hélium Editions, but they can now be found in several western countries and in many languages (Catalan, French, Dutch, English, German, Italian, Portuguese and Spanish, at least). The objective is to analyse their verbal text and their visual aspects produced by a sophisticated paper engineered to question how they achieve what seems to be one of their goals, the promotion of the readers' ecoliteracy (Orr, 1992) by his involvement in the reading process. This issue seems to be one of the main trends on children's literature in western societies nowadays, transcending the traditional and almost omnipresent role of scenario that nature plays in many children's narratives.